Counter-Public Spheres and Revival of the European Public Sphere - Wimmer, Jeffrey (Javnost-The Public, 2005)
From a theoretical point of view concepts of critical counter publicity are again widely discussed. However, both the socio-political relevance as well as the empirical dimension of this process . e.g. in how far counter-public spheres turn out to be a source of democratic public in reality . are mostly left out of consideration in the scientific discourse. The article first reconstructs descriptive and normative opinions on counter-public from a media-based perspective, and elaborates on the relationship between the public sphere, counter-public spheres, and new media. Then it discusses the potential of counter-public activities to revive the public sphere, particularly in the framework of the European Union. Two case studies of Europeanwide counter-public spheres are presented: the collective Luther Blissett and the network organisation of Attac. Their structural characteristics such as transnationality, network structure, and anti-copyright stance generate a new trans-European form of collective identity. As a result, the European integration may also gain (unintentionally) a new momentum.